Differentials for Lie algebras - Kuttler, Jochen (2015)
We develop a theory of relative Kähler differentials for Lie algebras. The main result is that the functor of relative differentials is representable, and that the universal object which represents it behaves properly with respect to étale base change. We illustrate how our construction yields a detailed analysis of the structure of derivations of multiloop algebras which is needed for the construction of Extended Affine Lie Algebras.